On the Efficiency of the Advancing-Front Surface Mesh Generation Algorithm. (December 2022) - Yu, Kaixin; Chen, Jianjun; Fu, Kejie; He, Jiangda; Zheng, Jianjing; Zheng, Yao
Abstract: An efficient advancing front algorithm is presented to create high-quality surface elements on CAD models. Various novel schemes are developed to improve the efficiency of the algorithm while not sacrificing its robustness and the resulting mesh quality. New features include a fast projection scheme that can perform robustly in case of badly defined surfaces, a procedure that computes the ideal point by an approach that can preserve the advantageous features of both the mapping and direct methods, and an octree data structure that can speed up the local search of all existing front nodes about the ideal point. To our knowledge, the proposed algorithm is one of the fastest algorithms for surface mesh generation. On an AMD Ryzen 5 3600 machine, the sequential version of the proposed algorithm can create a quality mesh at a speed of up to 100, 000 elements per second. This speed is more than 3 times higher than a state-of-the-art code can achieve. Another advantage of the proposed algorithm is its ability to maintain its high efficiency when millions or more elements are created on one single surface. In this circumstance, the efficiency of some state-of-the-arts codes slows down by one or two orders. After parallelized based on the taskflow approach, the proposed algorithm can create more than 1.6 million elements on real-world configurations in 7 s by using 6 computer cores. This speed is higher than a state-of-the-art commercial code can achieve by one order. Highlights: The efficiency of the AFT is dramatically improved without loss of its robustness. The improvement is rooted at contributions with respect to orthogonal projection, ideal point calculation and spatial data structures. The improved AFT maintains its efficiency at a high level when 80 million elements are created on one single surface. The improved AFT creates 1.6 million elements within 7 seconds, faster than a commercial counterpart by more than one order.